An Epimerase Gene Essential for Capsule Synthesis in Vibrio vulnificus - Zuppardo, Amy B. (American Society for Microbiology, 1998)
The extracellular capsule polysaccharide (CPS) of Vibrio vulnificus is a primary virulence factor which allows survival of the bacteria in the human host. To study the genes involved in expression of the capsule, we generated mutants that lost the ability to produce CPS following the insertion of a minitransposon into the genome of an encapsulated, clinical strain of V. vulnificus. A genomic region, from one nonencapsulated mutant, containing the transposon and flanking V. vulnificus DNA was cloned, and a probe complementary to the chromosomal DNA immediately adjacent to the transposon was used to locate this fragment in the genome of the encapsulated parent strain. The fragment, which contained a putative capsule gene, was cloned and, when supplied in trans, complemented the mutation in the nonencapsulated mutant to restore capsule production. In addition, virulence studies, using the 50% lethal dose assay, showed that the restoration of capsule production also restored the virulence of the organism. Sequence analysis of the gene disrupted by the transposon revealed that it matched a nucleotide-sugar epimerase of Vibrio cholerae O139, with 75 and 85% identities at the nucleotide and amino acid levels, respectively. In addition, computer analysis recognized epimerases of various organisms as highly similar to the putative epimerase of V. vulnificus. Finally, a combination of PCR amplification and Southern blotting showed that this epimerase is common to at least 10 strains of V. vulnificus that each express a serologically distinct CPS. Our results indicate that the epimerase gene is essential for capsule expression in V. vulnificus.